Attitude of women towards the use of family planning information in Abeokuta South Local Government Area of Ogun State, Nigeria (2018)
Women of child bearing age need information for their development in all aspects of life. One of such crucial information they require for optimum living is family planning information (FPI). Effective use of FPI, however, depends on the attitude of women towards it. It has been established that women’s poor attitudes towards FPI, as a result of many factors, have caused accelerated increase in population growth, high rate of unwanted pregnancies, increased sexually transmitted diseases, and illegal abortion, among others. It is against this background that this research examined the attitude of women towards the use of family planning information in Abeokuta South Local Government Area of Ogun State, Nigeria. Descriptive survey design was adopted for the study and systematic random sampling technique was used to select the sample size of 250 women o: child bearing age (15-49 years) in Abeokuta South Local Government Area of Ogun State, Nigeria. Questionnaire was the main research instrument and data was analysed using descriptive statistics such as frequencies and percentages for the three research questions. Results showed that most of the respondents have heard about family planning information, some have adopted it while others did not because of fear of its side effects, lack of awareness and partner’s disagreement. Awareness of FPI was found to be average but its level of use was low.